Intimate partner violence, contextual factors and under-5 mortality: a multilevel analysis of cross-sectional surveys from 20 Sub-Saharan African countries - Sanni Yaya; Seun Stephen Anjorin; Sunday A Adedini (BMJ Global Health)
Background Under-5 mortality remains a public health concern in low-income and middle-income countries. Africa contributes about one-fifth of the burden of global under-5 mortality; intimate partner violence (IPV) and polygyny, which are highly prevalent on the continent, have been linked to under-5 mortality at the individual level. This study examined the relationship between IPV and polygyny as contextual factors and the experience of under-5 mortality among women in Sub-Saharan Africa (SSA).Methods We used data from the Demographic and Health Surveys (DHS) of 20 African countries with available data between 2010 and 2018 as of April 2020. We defined the experience of under-5 mortality as a woman’s loss of at least one child before their fifth birthday. The DHS primary sampling unit was used to define contextual factors. The study involved a multilevel logistic regression analysis of 227 121 women of childbearing age (15–49).Results A quarter (24.5%) of women have lost at least one child under 5 years old, more than two-thirds (40.1%) have experienced at least one form of IPV, and about two-thirds of women were in polygynous union. Our multilevel logistic regression showed that parity, polygynous union and experience of IPV were strongly associated with women’s experience of under-5 mortality. The results showed that 39.9% and 19.2% of variances in odds of a woman losing a child before their fifth birthday are attributable to community-level and country-level factors, respectively. Contextual prevalence of IPV, polygynous union and gender equity attenuate the strength of associations observed at the individual level. The interaction between contextual prevalence of polygyny and IPV exacerbates the risk of under-5 mortality. Women in SSA countries with higher Human Development Index were less likely to experience under-5 mortality.Conclusion This study established that beyond individual-level effects, contextual prevalence of IPV and polygyny and their interactions shape women’s experience of under-5 mortality in Africa. In designing policies and interventions to address under-5 mortality, contextual factors, especially those linked to culturally laden social norms and practices, must be considered to ensure effectiveness and sustainable impact.